Knowledge of and self-expressed stigma for COVID-19 vaccination among pre-university students in a college in South India: A cross-sectional study - N G Prajakta; Sanjeev B Chougule; Ashok M Kamat; K Laxmi; L Ananda Kumar; Reena Verma; Rajesh Kamath (Wolters Kluwer Medknow Publications, 2024)
Background: Coronavirus disease 2019 (COVID-19) is a contagious infection characterized by severe acute respiratory syndrome (SARS-CoV-2). Safe and effective vaccines are game-changers in the global vision of marking an end to the challenges posed by the COVID-19 pandemic. However, vaccine hesitancy due to perceived stigma and misinformation is a grave cause of concern. Objectives: To assess pre-university students' self-expressed stigma regarding COVID-19 vaccination and its association with their knowledge. Materials and Methods: A cross-sectional study was adopted for this research. A structured questionnaire approach was used to gather data from 384 students purposively at the selected pre-university college. The structured questionnaire consisted of three sections that explored the socio-demographic characteristics of the study participants, knowledge of vaccination, and self-expressed stigma, respectively. A total of 384 respondents took part in the study. Results: The study observes a low positive relationship (r = 0.25, P < 0.01) between knowledge and self-expressed stigma toward vaccination. Further, it was observed that participants from rural backgrounds had lower knowledge and self-expressed stigma scores than participants from urban settings. It is pertinent to note that participants with other sources of information had higher knowledge than those who used the internet, friends/peers, or newspapers. Both of the aforementioned findings are statistically significant. Conclusion: The interventions should revive trust in national health authorities, structured awareness campaigns by government agencies, and media coverage about the safety and efficacy of vaccines. In addition, it is also important to support citizens in ensuring that they have access to the right information from authentic sources in times of crisis.